Pengaruh Orientasi Wirausaha dan Orientasi Pasar Keunggulan Bersaing Berkelanjutan pada UMKM Perdagangan Batik Pasar Klewer di Surakarta) - Fitriyana Rahmawati Kusuma Putri; Sri Suryoko (Universitas Diponegoro, 2018)
Klewer market was a center market for Indonesian batik from all over the city across of Indonesia and also became one of Surakarta city’s icon. Klewer market get the predicate for being the largest textile manufacturing in Southeast Asia. Traders have been trading at the klewer market since years when the ability business doers that determine their business continue to grow. Entrepreneurial orientation traits that can combine any combination to produce the value-added benefits that bigger than before. Cannot have developed in the absence of overfishing by customers and competitors where the orientation of market is something important in every business. These products have other excellence than other competitors products in the market. The purpose of this research to know the orientation of entrepreneurs and orientation on excellence compete sustainable markets ' trading small and medium businesses Klewer’s Market. Type of this research is explanatory research, were selected from as many as 97 respondents who 21 years old minimum and minimum 5 years of business. The sampling method of collecting samples using purposive technique. Data was gathered through the questionnaire. Method of analysis of the data used exclusively on the spss 16 for windows. Based on the results of the analysis calculation spss 16 for windows can be explained that the results of the test the influence of directly between the entrepreneurial orientation and orientation on excellence compete sustainable research on the model this really shows you the results of the impact that positive and significant. Of the suggestions proposed to covering the ability to see market opportunities, and being pioneer. This is proven by the results of the count of f 22,802 greater than f 3,093 table indicating that high low orientation entrepreneurs and orientation of the market will affect sustainable competitive advantage in Surakarta Klewer markets trading businesses. The probes also strengthened by correlation analysis are classified as moderate by 0,572 alpha value and the results of the determination that of the variable 32,7 % sustainable competitive advantage can be explained by the orientation of entrepreneurs and orientation 32,7 % market. An increase in market to seek information, the art and appetites customers and to provide information education about the unique products to customers.